Preparation method and application of carbon felt loaded porous high-entropy alloy flow battery electrode based on electrochemical dealloying
Patent Information
- Application Number
- CN202610997135.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]针对现有碳毡电极催化活性不足以及高熵合金难以在碳毡表面有效负载的问题,本发明提供一种基于电化学脱合金化的碳毡负载多孔高熵合金液流电池电极及其制备方法
[0027]1、将电化学脱合金方法应用于液流电池电极改性,在碳毡表面原位构筑纳米多孔高熵合金催化层,解决了高熵合金难以在三维基底上有效负载的问题。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of flow battery electrode materials technology, specifically to a method for preparing and applying a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying. Background Technology
[0002] Flow batteries, as a large-scale energy storage technology, have broad application prospects in renewable energy grid integration and grid peak shaving due to their advantages such as high safety, long lifespan, and independent design of power and capacity. Common flow batteries include vanadium redox flow batteries, iron-chromium flow batteries, iron redox flow batteries, and zinc-based flow batteries. However, the overall performance of flow batteries is largely limited by electrode materials. Although the widely used carbon felt electrodes have good conductivity and chemical stability, their catalytic activity for the redox reactions of active materials is insufficient, requiring surface modification to improve electrochemical performance.
[0003] High-entropy alloys, as multi-principal-element alloys composed of five or more main elements, exhibit great potential in the field of catalysis due to their unique "cocktail effect," high-entropy effect, and lattice distortion effect. Studies have shown that high-entropy alloys can significantly enhance catalytic activity by optimizing the electronic structure and regulating the adsorption energy of reaction intermediates through multi-element synergistic effects. Simultaneously, the nanoporous structure possesses extremely high specific surface area and abundant active sites, which can further enhance catalytic performance.
[0004] Traditional high-entropy alloy catalysts are often prepared using methods such as vacuum melting and mechanical alloying, resulting in bulk or powder materials that are difficult to directly load onto the surface of carbon felt electrodes. Electrochemical deposition combined with dealloying technology provides a new approach for constructing nanoporous high-entropy alloys on three-dimensional substrates. By first co-depositing an alloy layer containing catalytically active and sacrificial components, and then selectively dissolving the sacrificial components, a high-entropy alloy catalyst layer with a nanoporous structure can be formed in situ on the carbon fiber surface. Summary of the Invention
[0005] To address the issues of insufficient catalytic activity in existing carbon felt electrodes and the difficulty in effectively loading high-entropy alloys onto the carbon felt surface, this invention provides a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying and its preparation method. This method employs a reverse "alloying-dealloying" approach, first co-depositing an alloy layer containing sacrificial components on the carbon fiber surface, then selectively etching away the sacrificial components to construct a highly catalytically active nanoporous high-entropy alloy layer in situ.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0008] (1) Pretreatment of carbon felt substrate: The carbon felt substrate is pretreated to introduce oxygen-containing functional groups to enhance the bonding force between the subsequent alloy layer and the carbon fiber.
[0009] (2) Co-deposition of multi-component alloy layer: A multi-component alloy layer containing at least five metal elements is co-deposited on the surface of the pretreated carbon fiber by electrochemical deposition or chemical plating to obtain carbon felt covered with alloy layer.
[0010] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer is placed in a corrosive medium for dealloying treatment. By utilizing the difference in thermodynamic stability between the catalytic active component and the sacrificial component in the medium, the sacrificial component is selectively dissolved, and a nanoporous high-entropy alloy structure is formed in situ on the carbon fiber surface.
[0011] (4) Post-processing: The dealloyed electrode is cleaned and dried to obtain a carbon felt-supported porous high-entropy alloy flow battery electrode.
[0012] Further, in step (1), the carbon felt substrate is polyacrylonitrile-based carbon felt, pitch-based carbon felt, adhesive-based carbon felt, or carbon paper; the pretreatment is to ultrasonically remove oil in acetone, ethanol, and deionized water for 10 to 30 minutes in sequence, with an ultrasonic frequency of 20 kHz to 200 kHz; then soak in 5 wt% to 30 wt% HNO3 or H2SO4 solution at 60 ℃ to 90 ℃ for 1 to 6 hours to introduce oxygen-containing functional groups, and finally wash with deionized water until neutral, and dry at 60 ℃ to 100 ℃ for 6 to 12 hours.
[0013] Further, in step (2), the multi-component alloy layer includes a catalytically active component and a sacrificial component; the catalytically active component is selected from at least four of Bi, Sn, Zr, Mn, Co, Cr, Fe, and Ni; the sacrificial component is selected from one or more of Zn, Al, and Mg; the total atomic percentage of the catalytically active component in the multi-component alloy layer is 30% to 80%, and the total atomic percentage of the sacrificial component is 20% to 70%.
[0014] Further, in step (2), when electrochemical deposition is used, the electrolyte contains a salt solution of at least five metal ions, the total concentration of metal ions is 0.01 mol / L to 1.0 mol / L, the pretreated carbon felt is used as the working electrode, the platinum sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. Electrochemical deposition is carried out at a constant potential, the deposition potential is -1.5V to -0.5V vs. SCE, the deposition time is 5 minutes to 60 minutes, and the deposition temperature is 25℃ to 60℃; the electrolyte also contains a complexing agent.
[0015] In step (2), when chemical plating is used, the plating solution contains a salt solution of at least five metal ions, a reducing agent and a complexing agent, the total concentration of metal ions is 0.01 mol / L to 0.5 mol / L, the reducing agent is sodium hypophosphite or sodium borohydride, the concentration is 0.1 mol / L to 1.0 mol / L, the plating time is 10 minutes to 120 minutes, and the temperature is 40℃ to 80℃.
[0016] Further, the complexing agent is one or more of sodium citrate, potassium sodium tartrate, or disodium ethylenediaminetetraacetate, and the concentration of the complexing agent is 0.05 mol / L to 0.5 mol / L.
[0017] Further, in step (3), the corrosive medium is an acidic solution or an alkaline solution. The acidic solution is a 0.1 mol / L to 2.0 mol / L H2SO4, HCl or HNO3 solution; the alkaline solution is a 0.1 mol / L to 2.0 mol / L NaOH or KOH solution.
[0018] Further, in step (3), the dealloying process is carried out using a constant potential method, a constant current method, or a cyclic voltammetry method; the potential range of the constant potential method is -1.0V~0.5V vs. SCE, and the processing time is 10 minutes to 120 minutes; the current density of the constant current method is 1mA / cm²~50mA / cm², and the processing time is 10 minutes to 120 minutes; the scanning potential range of the cyclic voltammetry method is -1.5V~0.5V vs. SCE, the scanning rate is 1mV / s~100mV / s, and the processing time is 10 minutes to 120 minutes.
[0019] Furthermore, in step (3), an inert gas is introduced for stirring or ultrasonic assistance during the dealloying process, with a gas flow rate of 10 mL / min to 100 mL / min and an ultrasonic power of 50 W to 300 W.
[0020] Further, in step (3), the elemental composition of the nanoporous high-entropy alloy structure is at least five metal elements, each element having an atomic percentage of 5% to 35%, and the alloy having a single-phase solid solution structure; the pore size and porosity of the nanoporous high-entropy alloy structure are controlled by adjusting the potential and time of the dealloying process. The higher the dealloying potential or the longer the time, the larger the pore size. The porosity of the nanoporous high-entropy alloy structure is 30% to 70%, the specific surface area is 10 m² / g to 50 m² / g, and the pore size distribution is 5 nm to 100 nm.
[0021] Further, in step (4), the cleaning is to rinse repeatedly with deionized water or ethanol 3 to 5 times; the drying is to dry in a vacuum drying oven at 60℃ to 100℃ for 6 to 12 hours.
[0022] This invention provides an application of the carbon felt-supported porous high-entropy alloy flow battery electrode prepared by the above method. In the field of flow battery electrode materials, the electrode is used as an electrode in all-vanadium redox flow batteries, iron-chromium flow batteries, all-iron flow batteries, and zinc-based flow batteries.
[0023] The design concept of this invention is:
[0024] This invention creatively applies a reverse "alloying-dealloying" approach to the modification of flow battery electrodes. First, a multi-component alloy layer containing catalytically active components (such as Bi, Sn, Zr, Mn, Co, Cr, Fe, Ni, etc.) and sacrificial components (such as Zn, Al, Mg, etc.) is co-deposited on the carbon fiber surface via electrochemical deposition or electroless plating. The elements in this alloy layer are uniformly mixed, forming a precursor for a high-entropy alloy. Subsequently, selective electrochemical dealloying is performed in a corrosive medium. Utilizing the difference in thermodynamic stability between the catalytically active and sacrificial components in the medium, the chemically active sacrificial component preferentially dissolves, while the catalytically active component is retained and undergoes surface diffusion and reconstruction, ultimately forming a high-entropy alloy layer with a nanoporous structure in situ on the carbon fiber surface.
[0025] This strategy has the following unique advantages: First, by selectively removing sacrificial components, a three-dimensional interconnected porous structure can be formed in situ, greatly increasing the exposed area of catalytic active sites; second, the surface diffusion and reconstruction of active components during dealloying helps to form a stable single-phase high-entropy alloy structure; third, the multiple scattering effect of the porous structure can enhance the contact probability between the active material and the catalytic site; and fourth, by adjusting the alloy composition and dealloying conditions, precise control of the pore size, porosity, and elemental composition of the porous structure can be achieved.
[0026] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0027] 1. The electrochemical dealloying method was applied to the modification of flow battery electrodes, and a nanoporous high-entropy alloy catalyst layer was constructed in situ on the carbon felt surface, which solved the problem that high-entropy alloys are difficult to be effectively loaded on three-dimensional substrates.
[0028] 2. By adjusting the alloy composition (sacrificial component ratio 20%~70%), the dealloying potential (-1.0V~0.5V) and time (10 minutes~120 minutes), the pore size of the nanoporous structure can be precisely controlled to be 5nm~100nm and the porosity to be 30%~70%.
[0029] 3. A variety of catalytically active metal combinations (such as Bi-Sn-Zr-Mn-Co, Cr-Fe-Ni-Co-Mn, etc.) can be selected to optimize the electronic structure and enhance catalytic activity by utilizing the high entropy effect.
[0030] 4. The nanoporous structure enables the electrode specific surface area to reach 10m² / g~50m² / g, which is 1~2 orders of magnitude higher than that of unmodified carbon felt, and the electrochemical active area is greatly increased.
[0031] 5. The synergistic effect of multiple elements and the high specific surface area of the nanoporous structure of high-entropy alloys reduce charge transfer resistance by 50% to 70%, thereby improving energy efficiency.
[0032] 6. The alloy layer forms a tight bond with the carbon fiber surface through electrochemical deposition. After dealloying, the porous structure grows in situ, which is not easy to fall off and the electrode has excellent cycle stability. Attached Figure Description
[0033] Figure 1 Scanning electron microscope image of the multi-component alloy layer prepared in Example 1 after deposition.
[0034] Figure 2 The transmission electron microscope (TEM) image shows the elemental distribution of the multi-component alloy layer prepared in Example 1 after deposition.
[0035] Figure 3 The image shows the X-ray diffraction results of the multi-component alloy layer prepared in Example 1 after deposition. Detailed Implementation
[0036] The technical solution of the present invention will be described in detail below with reference to the embodiments, but the scope of protection claimed by the present invention is not limited to the embodiments described.
[0037] This invention discloses a method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying, comprising the following steps and process methods:
[0038] In the specific implementation process, the carbon felt substrate is first pretreated to introduce oxygen-containing functional groups; then, a multi-component alloy layer is co-deposited by electrochemical deposition or chemical plating; subsequently, selective electrochemical dealloying is performed in a corrosive medium; and finally, the composite electrode is obtained after cleaning and drying.
[0039] (1) Substrate pretreatment: Cut the carbon felt substrate into 10cm×10cm sizes. The carbon felt substrate is polyacrylonitrile-based carbon felt, pitch-based carbon felt, adhesive-based carbon felt or carbon paper. It is ultrasonically cleaned in acetone, ethanol and deionized water for 10 minutes to 30 minutes respectively. Then, it is soaked in 5wt% to 30wt% HNO3 or H2SO4 solution at 60℃ to 90℃ for 1 hour to 6 hours to introduce oxygen-containing functional groups. It is repeatedly rinsed with deionized water until neutral and dried in a vacuum drying oven at 60℃ to 100℃ for 6 hours to 12 hours for later use.
[0040] (2) Co-deposition of multi-component alloy layer: A multi-component alloy layer containing at least five metal elements is co-deposited on the surface of the pretreated carbon fiber by electrochemical deposition or chemical plating to obtain carbon felt covered with alloy layer.
[0041] The multi-component alloy layer comprises a catalytically active component and a sacrificial component; the catalytically active component is selected from at least three metals exhibiting catalytic activity towards the vanadium redox couple, namely Bi, Sn, Zr, Mn, Co, Cr, Fe, and Ni; the sacrificial component is selected from one or more metals selected from Zn, Al, and Mg that are chemically active and can be selectively removed in subsequent etching steps; the total atomic percentage of the catalytically active component in the multi-component alloy layer is 30% to 80%, and the total atomic percentage of the sacrificial component is 20% to 70%.
[0042] When using electrochemical deposition, an electrolyte containing at least five metal ions is prepared, with a total metal ion concentration of 0.01 mol / L to 1.0 mol / L. A pretreated carbon felt is used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. Electrochemical deposition is performed at a constant potential, with a deposition potential of -1.5 V to -0.5 V vs. SCE, a deposition time of 5 minutes to 60 minutes, and a deposition temperature of 25°C to 60°C. After deposition, the electrode is removed, rinsed with deionized water, and dried at room temperature. The electrolyte also contains a complexing agent, which is one or more of sodium citrate, potassium sodium tartrate, or disodium ethylenediaminetetraacetate, with a complexing agent concentration of 0.05 mol / L to 0.5 mol / L.
[0043] When using chemical plating, the plating solution contains a salt solution of at least five metal ions, a reducing agent, and a complexing agent. The total concentration of metal ions is 0.01 mol / L to 0.5 mol / L. The reducing agent is sodium hypophosphite or sodium borohydride with a concentration of 0.1 mol / L to 1.0 mol / L. The plating time is 10 minutes to 120 minutes, and the temperature is 40℃ to 80℃.
[0044] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer is placed in a corrosive medium and dealloyed using the constant potential method, constant current method or cyclic voltammetry method. The difference in thermodynamic stability between the catalytic active component and the sacrificial component in the medium is utilized to selectively dissolve the sacrificial component and form a nanoporous high-entropy alloy structure in situ on the carbon fiber surface. During the process, an inert gas is introduced for stirring or ultrasonic assistance is provided. The gas flow rate is 10 mL / min to 100 mL / min and the ultrasonic power is 50 W to 300 W. The carbon fiber is removed after dealloying is completed.
[0045] The corrosive medium is an acidic solution or an alkaline solution. The acidic solution is a 0.1 mol / L to 2.0 mol / L H2SO4, HCl or HNO3 solution; the alkaline solution is a 0.1 mol / L to 2.0 mol / L NaOH or KOH solution.
[0046] The potential range of the constant potential method is -1.0V to 0.5V vs. SCE, and the processing time is 10 minutes to 120 minutes; the current density of the constant current method is 1mA / cm² to 50mA / cm², and the processing time is 10 minutes to 120 minutes.
[0047] (4) Post-treatment: The electrode after the dealloying treatment is rinsed repeatedly with deionized water or ethanol 3 to 5 times, and dried in a vacuum drying oven at 60℃ to 100℃ for 6 to 12 hours to obtain a carbon felt-supported porous high-entropy alloy flow battery electrode.
[0048] The raw materials and equipment used, such as carbon felt of different specifications and metal salts, are all commercially available.
[0049] The present invention will now be described in further detail through embodiments.
[0050] Example 1
[0051] A method for preparing a carbon felt-supported Bi-Sn-Zn-Mn-Co porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0052] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0053] (2) Co-deposition of multi-component alloy layer: An electrolyte containing Bi³⁺, Sn²⁺, Zn²⁺, Mn²⁺, and Co²⁺ was prepared, with each metal ion concentration of 0.02 mol / L and a total concentration of 0.1 mol / L. 0.1 mol / L sodium citrate was added as a complexing agent. Using pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was carried out at -1.2 V vs. SCE potential for 30 minutes at a deposition temperature of 40 °C. After deposition, the carbon felt was rinsed with deionized water and dried at room temperature to obtain a carbon felt coated with an alloy layer. Figure 1 Scanning electron microscope images of multi-component alloy layers after deposition;
[0054] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a potential constant of 0.1 V vs. SCE to selectively dissolve Zn; nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after the dealloying was completed.
[0055] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-1.
[0056] Modified electrode CF-HEA-1: such as Figure 1 As shown, scanning electron microscopy reveals that the deposited alloy layer uniformly covers the carbon fiber surface, and after dealloying, it forms a three-dimensional interconnected nanoporous structure. Figure 2 The elemental distribution of the multi-component alloy layer prepared in Example 1 after deposition is shown by transmission electron microscopy. The transmission electron microscopy elemental distribution shows that Bi, Sn, Mn, and Co elements are uniformly distributed, and the Zn content is reduced to below 5 at%. Figure 3 The X-ray diffraction results for the multi-component alloy layer prepared in Example 1 after deposition show a single-phase face-centered cubic structure. The specific surface area of the modified carbon felt electrode CF-HEA-1 is increased to 18.5 m² / g, and the electrochemical active area is increased to 82.3 mF / cm². -2 The cells were assembled into a single vanadium redox flow battery and tested at a current density of 200 mA / cm², showing an energy efficiency of 86.2%.
[0057] Example 2
[0058] A method for preparing a carbon felt-supported Cr-Fe-Ni-Co-Mn porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0059] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0060] (2) Co-deposition of multi-component alloy layer: An electrolyte containing Cr³⁺, Fe²⁺, Ni²⁺, Co²⁺, and Mn²⁺ was prepared, with each metal ion concentration of 0.02 mol / L and a total concentration of 0.1 mol / L. 0.1 mol / L sodium citrate was added as a complexing agent, and 0.1 mol / L sodium hypophosphite as a reducing agent. The electroless plating time was 10 minutes, and the temperature was 40℃. After deposition, the layer was removed, rinsed with deionized water, and dried at room temperature.
[0061] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 90 minutes at a potential of 0.2 V vs. SCE using the constant potential method to selectively dissolve Mn. Nitrogen gas was introduced and stirred during the process. The carbon felt was removed after the dealloying was completed.
[0062] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-2.
[0063] Modified electrode CF-HEA-2: Scanning electron microscopy shows that the deposited alloy layer uniformly covers the carbon fiber surface, forming a three-dimensional interconnected nanoporous structure with a pore size of approximately 15-40 nm after dealloying; transmission electron microscopy shows that Cr, Fe, Ni, and Co elements are uniformly distributed, while the Mn content is reduced to below 8 at%; X-ray diffraction shows a single-face-centered cubic structure; the specific surface area is increased to 16.2 m² / g, and the electrochemically active area is increased to 75.8 mFcm. -2 The cells were assembled into a single vanadium redox flow battery and tested at a current density of 200 mA / cm², showing an energy efficiency of 85.5%.
[0064] Example 3
[0065] A method for preparing a carbon felt-supported Co-Cr-Fe-Ni-Zn porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0066] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0067] (2) Co-deposition of multi-component alloy layer: Prepare an electrolyte containing Co²⁺, Cr³⁺, Fe²⁺, Ni²⁺ and Zn²⁺, with each metal ion concentration of 0.02 mol / L and a total concentration of 0.1 mol / L. Add 0.1 mol / L potassium sodium tartrate as a complexing agent. Use pretreated carbon felt as the working electrode, platinum sheet as the counter electrode, and saturated calomel electrode as the reference electrode. Deposit for 35 minutes at a potential of -1.1 V vs. SCE and a deposition temperature of 40 °C. After deposition, remove the material, rinse with deionized water, and dry at room temperature.
[0068] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in 0.5 mol / L NaOH solution and dealloyed for 60 minutes at -0.8 V vs. SCE potential using the constant potential method to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The dealloying was completed and the carbon felt was removed.
[0069] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-3.
[0070] Modified electrode CF-HEA-3: Scanning electron microscopy shows that the deposited alloy layer uniformly covers the carbon fiber surface, forming a three-dimensional interconnected nanoporous structure with a pore size of approximately 20-45 nm after dealloying; transmission electron microscopy shows that Co, Cr, Fe, and Ni are uniformly distributed, while the Zn content is reduced to below 6 at%; X-ray diffraction shows a single-faceted cubic structure; the specific surface area is increased to 17.3 m² / g, and the electrochemically active area is increased to 79.1 mFcm. -2 The cells were assembled into a single vanadium redox flow battery and tested at a current density of 200 mA / cm², showing an energy efficiency of 85.8%.
[0071] Example 4
[0072] A method for preparing a carbon felt-supported Bi-Sn-Zr-Mn-Co porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0073] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0074] (2) Co-deposition of multi-component alloy layers: a mixture containing Bi³⁺, Sn²⁺, and Zr was prepared. 4+ An electrolyte of Mn²⁺ and Co²⁺ was prepared, with each metal ion concentration of 0.015 mol / L and a total concentration of 0.075 mol / L. 0.1 mol / L sodium citrate was added as a complexing agent, and 0.1 mol / L sodium hypophosphite as a reducing agent. The electroless plating process lasted 60 minutes at 60°C. After deposition, the plating was rinsed with deionized water and dried at room temperature.
[0075] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a potential constant of 0.1 V vs. SCE to selectively dissolve Mn and Zr. Nitrogen gas was introduced and stirred during the process. The dealloying was completed and the carbon felt was removed.
[0076] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-4.
[0077] Modified electrode CF-HEA-4: Scanning electron microscopy shows that the deposited alloy layer uniformly covers the carbon fiber surface, forming a three-dimensional interconnected nanoporous structure with pore sizes of approximately 15 nm to 35 nm after dealloying; transmission electron microscopy shows uniform distribution of Bi, Sn, and Co elements, with significantly reduced Mn and Zr contents; X-ray diffraction reveals a face-centered cubic structure; the specific surface area is increased to 15.8 m² / g, and the electrochemically active area is increased to 73.2 mF / cm². -2 The cells were assembled into a single vanadium redox flow battery and tested at a current density of 200 mA / cm², showing an energy efficiency of 84.9%.
[0078] Example 5
[0079] A method for preparing a carbon felt-supported Bi-Sn-Zr-Mn-Co-Zn porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0080] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0081] (2) Co-deposition of multi-component alloy layers: a mixture containing Bi³⁺, Sn²⁺, and Zr was prepared. 2+ An electrolyte of Bi, Sn, Zr, Mn, and Co was prepared, with Bi, Sn, Zr, Mn, and Co concentrations of 0.015 mol / L each, Zn concentration of 0.04 mol / L, and a total concentration of 0.115 mol / L. Sodium citrate (0.1 mol / L) was added as a complexing agent. Pretreated carbon felt was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. Deposition was performed at -1.2 V vs. SCE potential for 30 minutes at a deposition temperature of 40 °C. After deposition, the electrode was rinsed with deionized water and dried at room temperature.
[0082] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a potential constant of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The dealloying was completed and the carbon felt was removed.
[0083] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-5.
[0084] Modified electrode CF-HEA-5: Scanning electron microscopy shows a more developed porous structure after dealloying, with pore sizes of approximately 25nm~60nm and a porosity of approximately 60%; transmission electron microscopy shows uniform distribution of Bi, Sn, Zr, Mn, and Co elements; the specific surface area is increased to 21.2m² / g, and the electrochemical active area is increased to 89.5mFcm. -2 The cells were assembled into a single all-ferric flow battery and tested at a current density of 80 mA / cm², showing an energy efficiency of 87.0%.
[0085] Example 6
[0086] A method for preparing a carbon felt-supported Bi-Sn-Zn-Mn-Co porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0087] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0088] (2) Co-deposition of multi-component alloy layer: An electrolyte containing Bi³⁺, Sn²⁺, Mn²⁺, Co²⁺, and Zn²⁺ was prepared, wherein the concentrations of Bi, Sn, Mn, and Co were all 0.01 mol / L, the concentration of Zn was 0.06 mol / L, and the total concentration was 0.1 mol / L. 0.1 mol / L sodium citrate was added as a complexing agent; 1.0 mol / L sodium hypophosphite was added as a reducing agent. The electroless plating time was 120 minutes, and the temperature was 80℃. After deposition, the layer was removed, rinsed with deionized water, and dried at room temperature.
[0089] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a potential constant of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The dealloying was completed and the carbon felt was removed.
[0090] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-6.
[0091] Modified electrode CF-HEA-6: Scanning electron microscopy shows a highly developed porous structure after dealloying, but some areas exhibit pore wall collapse. The pore size is approximately 30 nm to 80 nm, and the porosity is approximately 65%. Transmission electron microscopy shows the distribution of Bi, Sn, Mn, and Co elements. The specific surface area is increased to 20.5 m² / g, and the electrochemically active area is increased to 86.7 mF / cm². -2 The cells were assembled into a single all-ferric flow battery and tested at a current density of 50 mA / cm², showing an energy efficiency of 86.5%.
[0092] Example 7
[0093] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0094] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0095] (2) Co-deposition of multi-component alloy layers: Same as in Example 1.
[0096] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 30 minutes at a constant potential of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after dealloying was completed.
[0097] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-7.
[0098] Modified electrode CF-HEA-7: Scanning electron microscopy revealed that after dealloying, a nanoporous structure was formed, but the pore size was small, approximately 10 nm to 25 nm, with a porosity of approximately 35%; the specific surface area increased to 14.2 m² / g, and the electrochemical active area increased to 68.5 mF / cm². -2 The assembled iron-chromium redox flow battery single cell was tested at a current density of 70 mA / cm², and the energy efficiency was 83.8%.
[0099] Example 8
[0100] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0101] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0102] (2) Co-deposition of multi-component alloy layers: Same as in Example 1;
[0103] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 120 minutes at a potential of 0.1 V vs. SCE using the constant potential method to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The carbon felt was removed after the dealloying was completed.
[0104] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-8.
[0105] Modified electrode CF-HEA-8: Scanning electron microscopy shows that after dealloying, the porous structure has a larger pore size, approximately 40nm~70nm, and a porosity of approximately 55%; the specific surface area is increased to 17.8m² / g, and the electrochemical active area is increased to 80.3mFcm. -2 The cells were assembled into a single vanadium redox flow battery and tested at a current density of 200 mA / cm², showing an energy efficiency of 85.5%.
[0106] Example 9
[0107] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0108] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0109] (2) Co-deposition of multi-component alloy layers: Same as in Example 1;
[0110] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a potential of 0.3 V vs. SCE using the constant potential method to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The carbon felt was removed after the dealloying was completed.
[0111] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-9.
[0112] Modified electrode CF-HEA-9: Scanning electron microscopy shows that after dealloying, the porous structure has a larger pore size, approximately 35nm~65nm, and a porosity of approximately 58%; the specific surface area is increased to 18.9m² / g, and the electrochemical active area is increased to 83.7mFcm. -2 The zinc-bromine flow battery was assembled into a single cell and tested at a current density of 45 mA / cm², showing an energy efficiency of 86.0%.
[0113] Example 10
[0114] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0115] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0116] (2) Co-deposition of multi-component alloy layer: Prepare an electrolyte containing Bi³⁺, Sn²⁺, Mn²⁺, Co²⁺ and Al³⁺, with each metal ion concentration of 0.02 mol / L and a total concentration of 0.1 mol / L. Add 0.1 mol / L sodium citrate as a complexing agent. Use pretreated carbon felt as the working electrode, platinum sheet as the counter electrode, and saturated calomel electrode as the reference electrode. Deposit for 50 minutes at -1.4 V vs. SCE potential and at a deposition temperature of 50 °C. After deposition, remove the material, rinse with deionized water, and dry at room temperature.
[0117] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in 0.5 mol / L NaOH solution and dealloyed for 60 minutes at -0.8 V vs. SCE potential using the constant potential method to selectively dissolve Al; nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after the dealloying was completed.
[0118] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-10.
[0119] Modified electrode CF-HEA-10: Scanning electron microscopy shows that after dealloying, a nanoporous structure is formed with a pore size of approximately 15-40 nm; transmission electron microscopy shows that Bi, Sn, Mn, and Co are uniformly distributed; the specific surface area is increased to 15.3 m² / g, and the electrochemical active area is increased to 72.1 mFcm. -2 The zinc-bromine flow battery was assembled into a single cell and tested at a current density of 50 mA / cm², showing an energy efficiency of 84.5%.
[0120] Example 11
[0121] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0122] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0123] (2) Co-deposition of multi-component alloy layers: An electrolyte containing Bi³⁺, Sn²⁺, Mn²⁺, Co²⁺, and Mg²⁺ was prepared, with each metal ion concentration of 0.02 mol / L and a total concentration of 0.1 mol / L. 0.1 mol / L sodium citrate was added as a complexing agent. A pretreated carbon felt was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. Deposition was carried out at -1.5 V vs. SCE potential for 60 minutes at a deposition temperature of 50 °C. After deposition, the layers were rinsed with deionized water and dried at room temperature.
[0124] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a potential constant of 0.1 V vs. SCE to selectively dissolve Mg; nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after the dealloying was completed.
[0125] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-12.
[0126] Modified electrode CF-HEA-12: Scanning electron microscopy shows that after dealloying, a nanoporous structure is formed with a pore size of approximately 10-35 nm; transmission electron microscopy shows that Bi, Sn, Mn, and Co are uniformly distributed; the specific surface area is increased to 14.8 m² / g, and the electrochemical active area is increased to 70.5 mFcm. -2 Assembled into a single all-ferric flow battery, the energy efficiency was 77.2% when tested at a current density of 100 mA / cm².
[0127] Example 12
[0128] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0129] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0130] (2) Co-deposition of multi-component alloy layers: Same as in Example 1;
[0131] (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a potential constant of 0.1 V vs. SCE. Ultrasonic assistance was applied during the dealloying process with an ultrasonic power of 200 W to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The dealloying was completed and the carbon felt was removed.
[0132] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-13.
[0133] Modified electrode CF-HEA-12: Scanning electron microscopy shows a more uniform porous structure after dealloying, with pore sizes of approximately 20nm~45nm and narrower pore distribution; transmission electron microscopy shows uniform distribution of Bi, Sn, Mn, and Co elements; specific surface area increased to 19.2m² / g, and electrochemical active area increased to 85.6mFcm. -2 The cells were assembled into a single vanadium redox flow battery and tested at a current density of 200 mA / cm², showing an energy efficiency of 86.5%.
[0134] Example 13
[0135] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0136] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0137] (2) Co-deposition of multi-component alloy layer: The deposition potential was changed to -1.0V vs. SCE, and the rest was the same as in Example 1;
[0138] (3) Selective electrochemical dealloying: Same as Example 1;
[0139] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-14.
[0140] Modified electrode CF-HEA-13: Scanning electron microscopy shows a thin deposited layer with a porous structure after dealloying, exhibiting a pore size of approximately 15nm~30nm and a low loading. The specific surface area is increased to 13.5m² / g, and the electrochemical active area is increased to 65.8mFcm. -2 The cells were assembled into a single all-ferric flow battery and tested at a current density of 100 mA / cm², showing an energy efficiency of 73.0%.
[0141] Example 14
[0142] A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying includes the following steps:
[0143] (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces, and clean it by ultrasonication for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt%HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0144] (2) Co-deposition of multi-component alloy layers: The deposition time was changed to 20 minutes, and the rest was the same as in Example 1;
[0145] (3) Selective electrochemical dealloying: Same as Example 1;
[0146] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-HEA-15.
[0147] Modified electrode CF-HEA-15: Scanning electron microscopy shows a thin deposited layer with a porous structure after dealloying, exhibiting a pore size of approximately 15nm~35nm and a low loading; the specific surface area is increased to 12.8m² / g, and the electrochemical active area is increased to 62.3mFcm. -2 The cells were assembled into a single vanadium redox flow battery and tested at a current density of 150 mA / cm², showing an energy efficiency of 82.5%.
[0148] The results of the examples demonstrate that, employing the "alloying-dealloying" reverse approach of this invention, a nanoporous high-entropy alloy catalytic layer can be successfully constructed on the surface of a carbon felt electrode using a simple and controllable electrochemical method. The electronic structure and catalytic performance of the high-entropy alloy can be controlled by adjusting the types of catalytically active components (Bi, Sn, Zr, Mn, Co, Cr, Fe, Ni, etc.) in the alloy composition; the porosity and pore size of the porous structure can be precisely controlled by adjusting the proportion of sacrificial components (Zn, Al, Mg); the thickness and compositional uniformity of the alloy layer can be controlled by adjusting the electrochemical deposition potential (-1.5V to -0.5V) and time (5 minutes to 60 minutes); and the pore size and the degree of development of the porous structure can be further controlled by adjusting the dealloying potential (-1.0V to 0.5V) and time (10 minutes to 120 minutes). The prepared porous high-entropy alloy modified electrode, with its unique nanoporous structure (specific surface area 10~50 m² / g) and the multi-element synergistic effect of the high-entropy alloy, significantly enhances the catalytic activity for the redox reaction of active materials in flow batteries, reduces charge transfer resistance by 50%~70%, and increases the electrochemical active area to 60~90 mFcm. -2 This electrode, through its inherent nanoporous high-entropy alloy structure design, effectively coordinates the multiple requirements of flow battery electrodes for high catalytic activity, high specific surface area, and rapid electron conduction, providing a key electrode material solution for the development of next-generation high-performance, high-power-density flow batteries.
Claims
1. A method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying, characterized in that, Includes the following steps: (1) Pretreatment of carbon felt substrate: The carbon felt substrate is pretreated to introduce oxygen-containing functional groups to enhance the bonding force between the subsequent alloy layer and the carbon fiber. (2) Co-deposition of multi-component alloy layer: A multi-component alloy layer containing at least five metal elements is co-deposited on the surface of the pretreated carbon fiber by electrochemical deposition or chemical plating to obtain carbon felt covered with alloy layer. (3) Selective electrochemical dealloying: The carbon felt coated with the alloy layer is placed in a corrosive medium for dealloying treatment. By utilizing the difference in thermodynamic stability between the catalytic active component and the sacrificial component in the medium, the sacrificial component is selectively dissolved, and a nanoporous high-entropy alloy structure is formed in situ on the carbon fiber surface. (4) Post-processing: The dealloyed electrode is cleaned and dried to obtain a carbon felt-supported porous high-entropy alloy flow battery electrode.
2. The method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying according to claim 1, characterized in that, In step (1), the carbon felt substrate is polyacrylonitrile-based carbon felt, pitch-based carbon felt, adhesive-based carbon felt, or carbon paper; the pretreatment is to ultrasonically remove oil in acetone, ethanol, and deionized water for 10 to 30 minutes in sequence, with an ultrasonic frequency of 20 kHz to 200 kHz; then soak in 5 wt% to 30 wt% HNO3 or H2SO4 solution at 60 ℃ to 90 ℃ for 1 to 6 hours to introduce oxygen-containing functional groups, and finally wash with deionized water until neutral, and dry at 60 ℃ to 100 ℃ for 6 to 12 hours.
3. The method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying according to claim 1, characterized in that, In step (2), the multi-component alloy layer includes a catalytically active component and a sacrificial component; the catalytically active component is selected from at least four of Bi, Sn, Zr, Mn, Co, Cr, Fe, and Ni; the sacrificial component is selected from one or more of Zn, Al, and Mg; the total atomic percentage of the catalytically active component in the multi-component alloy layer is 30% to 80%, and the total atomic percentage of the sacrificial component is 20% to 70%.
4. The method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying according to claim 1, characterized in that, In step (2), when electrochemical deposition is used, the electrolyte contains a salt solution of at least five metal ions, with a total metal ion concentration of 0.01 mol / L to 1.0 mol / L. A pretreated carbon felt is used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. Electrochemical deposition is performed at a constant potential, with a deposition potential of -1.5 V to -0.5 V vs. SCE, a deposition time of 5 minutes to 60 minutes, and a deposition temperature of 25°C to 60°C. The electrolyte also contains a complexing agent. In step (2), when using chemical plating, the plating solution contains a salt solution of at least five metal ions, a reducing agent and a complexing agent, the total concentration of metal ions is 0.01 mol / L to 0.5 mol / L, the reducing agent is sodium hypophosphite or sodium borohydride, the concentration is 0.1 mol / L to 1.0 mol / L, the plating time is 10 minutes to 120 minutes, and the temperature is 40℃ to 80℃. The complexing agent is one or more of sodium citrate, potassium sodium tartrate, or disodium ethylenediaminetetraacetate, and the concentration of the complexing agent is 0.05 mol / L to 0.5 mol / L.
5. The method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying according to claim 1, characterized in that, In step (3), the corrosive medium is an acidic solution or an alkaline solution. The acidic solution is a 0.1 mol / L to 2.0 mol / L H2SO4, HCl or HNO3 solution; the alkaline solution is a 0.1 mol / L to 2.0 mol / L NaOH or KOH solution.
6. The method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying according to claim 1, characterized in that, In step (3), the dealloying process is performed using a constant potential method, a constant current method, or a cyclic voltammetry method. The potential range of the constant potential method is -1.0V to 0.5V vs. SCE, and the processing time is 10 minutes to 120 minutes. The current density of the constant current method is 1mA / cm² to 50mA / cm², and the processing time is 10 minutes to 120 minutes. The scanning potential range of the cyclic voltammetry method is -1.5V to 0.5V vs. SCE, the scanning rate is 1mV / s to 100mV / s, and the processing time is 10 minutes to 120 minutes.
7. The method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying according to claim 1, characterized in that, In step (3), an inert gas is introduced for stirring or ultrasonic assistance during the dealloying process. The gas flow rate is 10 mL / min to 100 mL / min and the ultrasonic power is 50 W to 300 W.
8. The method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying according to claim 1, characterized in that, In step (3), the elemental composition of the nanoporous high-entropy alloy structure is at least five metal elements, each element having an atomic percentage of 5% to 35%, and the alloy is a single-phase solid solution structure. The pore size and porosity of the nanoporous high-entropy alloy structure are controlled by adjusting the potential and time of the dealloying process. The higher the dealloying potential or the longer the time, the larger the pore size. The porosity of the nanoporous high-entropy alloy structure is 30% to 70%, the specific surface area is 10 m² / g to 50 m² / g, and the pore size distribution is 5 nm to 100 nm.
9. The method for preparing a carbon felt-supported porous high-entropy alloy flow battery electrode based on electrochemical dealloying according to claim 1, characterized in that, In step (4), the cleaning is to rinse repeatedly with deionized water or ethanol 3 to 5 times; the drying is to dry in a vacuum drying oven at 60℃ to 100℃ for 6 to 12 hours.
10. An application of a carbon felt-supported porous high-entropy alloy flow battery electrode obtained by the preparation method according to any one of claims 1-9, characterized in that, In the field of flow battery electrode materials, the electrode is used as an electrode in vanadium redox flow batteries, iron-chromium flow batteries, iron redox flow batteries, and zinc-based flow batteries.